TweetShort Text Data Analysis on COVID-19 Out Break - V. Laxmi Narasamma ,Dr. M. Sreedevi, Dr G.Vijay Kumar (International Journal of Advanced Science and Technology, 2020)
World Health Organization announced COVID19 outbreak as a pandemic in the month of march 2020.This Pandamic virus was  originated from dragan country China, it is a big  pandemic  virus has been attacking  and killinglakhs  of people through out of the world. While this pandemic has continued to affect the lives of millions, a number of countries have resorted to complete lockdown. During this lockdown, people have taken social networks to express their feelings andfindawaytocalmthemselvesdown.In this work temporal sentiment analysis shown on covid-19 tweets over time april 16th to april 30th.This workmainly focused on polarity score of each tweet with Vader Algorithm in NLP and classified the scores based on compound polarity value finally  tweets are identified  into three major sentiment classes such as positive,negative and neutral based  on compound polarity score.This work also focuses data visualization by showing sentiment score plot,  Temporal sentiments over time.